Histopathological Evaluation of Primary Teeth after Pulp Capping with Calcium-Enriched Mixture and Bioactive Glass - Haghgoo, Roza; Asgary, Saeed; Montazeri, Roshanak (Iranian Endodontic Journal, 2018)
Introduction: Direct pulp capping (DPC) is a conservative vital pulp therapy, which has some limitations in primary dentition. The aim of this study was to evaluate pulpal response of primary teeth after DPC with two biocompatible materials naming calcium-enriched mixture (CEM) and bioactive glass (BAG). Methods and Materials: This study was designed as a randomized clinical trial. After obtaining informed consent, 20 sound primary canines scheduled for orthodontic extraction, were selected. Following mechanical pulp exposure, the exposed site was capped with either CEM cement or BAG and then restored with amalgam. Teeth were extracted after two months and examined histopathologically. Parameters of hard tissue bridge (HTB) formation, its type and pulpal inflammation scores, were compared between the two groups. Data were analysed using the Fisher’s exact test. Results: All CEM specimens showed inflammation scores of 0 (less than 10%). In the BAG group, inflammation scores of 0, 1 and 2 were observed in 7, 2 and 1 specimens, respectively. Fisher’s exact test showed no significant differences (P>0.05). All CEM specimens (100%) formed HTB, which was irregular in all cases. In 7 of 10 teeth in BAG, HTB formed and was irregular. Fisher’s exact test revealed no significant differences between the two groups in this regard (P<0.001). Conclusion: Both CEM and BAG are suitable DPC agents in terms of HTB formation and pulp inflammation scores. Keywords: Bioactive Glass; Calcium-Enriched Mixture; Direct Pulp Capping; Primary Teeth